Lokalitas Tafsir Nusantara Dalam Kitab Taj Al-Muslimin min Kalami Rabbi Al-Alamin - Siti Robikah; Kuni Muyassaroh (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2019)
The treasure of interpretation in Indonesia from generation to generation has developed and is very relevant to be studied further. The development of interpretation studies will have a positive impact on the advancement of Indonesian culture as well. So many interpretations in regional languages are evenly distributed in Indonesia, one of them is the interpretation of Taj Al-Muslimin min Kalami Rabbi Al-Alamin, the second work of KH Misbah Musthafa. This interpretation which only consisted of 4 volumes did not finish until 30 juz because KH Misbah Mustafa had died. This interpretation work uses Javanese and is written using the pegon script. Pegon script is a script only known since the colonial period which was used by Indonesians to give news to others so that the invaders could not read. This then developed into a pattern of writing the interpretation of the archipelago, especially in Java. By using a historical approach and a qualitative method with descriptive analysis, this paper examines in detail the aspects of locality in the second interpretation of KH Misbah Mustafa. Finally, it can be mapped into three aspects of locality, namely locality in appearance, communication and interpretation, all of which are contained in the second book of interpretation by KH Misbah Mustafa.